Normal behavior of plasma procalcitonin in adolescents undergoing surgery for scoliosis. (March 2014) - Syvänen, J.; Peltola, V.; Pajulo, O.; Ruuskanen, O.; Mertsola, J.; Helenius, I.
Background and Aims: Surgical site infections are relatively common after spinal deformity surgery. Early detection of deep wound infections is important, since it may allow retention of spinal instrumentation. However, serum C-reactive protein and erythrocyte sedimentation rate may remain elevated for almost 6 weeks, making differential diagnosis of systemic inflammatory response and acute deep bacterial wound infection difficult. Plasma procalcitonin has been suggested to be a useful indicator for bacterial infection. However, there are no studies evaluating behavior of procalcitonin in patients undergoing major spine surgery with instrumentation. Materials and Methods: A total of 50 consecutive adolescents (37 idiopathic scoliosis and 13 neuromuscular scoliosis, mean age = 15 years at surgery and follow-up time = 21 months (range = 12–29 months)) undergoing scoliosis surgery participated in this prospective follow-up study. White blood cell count, serum C-reactive protein, and plasma procalcitonin levels were measured on the day before surgery, on the day of surgery, and daily thereafter for 1 week. None of the patients developed signs of acute or delayed wound infection during the follow-up period; however, two neuromuscular scoliosis patients developed severe postoperative pneumonia, and their inflammatory parameter data will be reported separately. Results: Plasma procalcitonin levels peaked on the first postoperative day (mean = 0.19 ng/mL, range = 0.04–1.29 ng/mL), and mean values were less than 0.5 ng/mL during the whole first postoperative week, while C-reactive protein remained elevated during the whole first postoperative week (highest mean value = 63.8 mg/L (range = 5–248 mg/L) on third postoperative day). Patients with idiopathic scoliosis had lower C-reactive protein levels (p < 0.05 from first to sixth postoperative day) and lower procalcitonin levels (p < 0.05 from third to seventh postoperative day) than neuromuscular scoliosis patients. Two patients with postoperative pneumonia showed elevated procalcitonin values over the whole postoperative week (22.34 ng/mL and 0.72 ng/mL highest values, respectively). Conclusions: Elevated plasma procalcitonin levels seem useful when excluding acute deep wound infection from systemic inflammatory response.